﻿Lepisorus medioximus (Polypodiales, Polypodiaceae), a new species from Shan State of Myanmar - Tao Fujiwara; Phyo Kay Khine; Kiyotaka Hori; Thant Shin; Noriaki Murakami; Harald Schneider (PhytoKeys, 2022)
A new species of the species-rich fern genus Lepisorus (Polypodiales, Polypodiaceae) has been found to occur in Shan state, Myanmar. Lepisorus medioximus is described based on morphological characters and phylogenetic evidence. Phylogenetic analyses showed that the specimens of L. medioximus formed a distinct clade nested in the Pseudovittaria clade. The morphological comparison demonstrated that the species is distinct from phylogenetically related species, namely L. elegans, L. contortus, and L. tosaensis, in the morphology of the rhizome scales, size, and shape of the lamina, position of sori, and paraphyses.